2014
DOI: 10.1016/j.sbspro.2014.07.147
|View full text |Cite
|
Sign up to set email alerts
|

Austerity Measures in Greece and their Impact on Higher Education

Abstract: The present study examines the impact of austerity measures on the academic community. The Technological Educational Institute of Athens served as our case study. It was selected because it is the second largest higher education institution in Greece, and has students of a diverse socio-economic background. Data were obtained through an analysis of institution financial statements and other documents depicting budgets, human resources, infrastructure, in an attempt to study their impact on the resulting qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
(1 reference statement)
0
13
0
1
Order By: Relevance
“…In this direction, accumulative evidence has shown that austerity measures during past years have led to a deterioration in the quality of health services, [15][16][17][18] an increase in mortality 19,20 and a lower level in education. 21,22 Countries with reduced resources and large cuts in health expenditure such as Greece cannot keep pace with the rapid growth rates of countries such as Belgium and Switzerland. However, the study by Squires and Anderson 23 showed that spending more on healthcare does not result in better outcomes or longer life expectancy of each country's patients, possibly showing the loose correlation between ROSC rates and life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, accumulative evidence has shown that austerity measures during past years have led to a deterioration in the quality of health services, [15][16][17][18] an increase in mortality 19,20 and a lower level in education. 21,22 Countries with reduced resources and large cuts in health expenditure such as Greece cannot keep pace with the rapid growth rates of countries such as Belgium and Switzerland. However, the study by Squires and Anderson 23 showed that spending more on healthcare does not result in better outcomes or longer life expectancy of each country's patients, possibly showing the loose correlation between ROSC rates and life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…It often has serious well-being and psychological repercussions (Mouzakis, 2017). In the Greek case, the pervasive sense of distrust (Koniordos, 2014), uncertainty, and lack of security, led a large part of the workforce to seek employment abroad (Giousmpasoglou et al, 2016;Koulouris et al, 2014), forming distinct drivers of migration (Carling and Collins, 2018). The so-called 'brain overflow' contributed in this direction, that is, the inability of a country to absorb the domestic highly skilled work population (Iravani, 2011).…”
Section: Why Are They Leaving Today?mentioning
confidence: 99%
“…There is very little evidence that the crisis engendered serious innovation in university teaching, either in new forms of learning or in content. To the contrary, the introduction of good practices as observed worldwide, for example in students assessing teachers or in problem and case-based learning, seems to have slowed down (see for a Greek example: Koulouris et al 2014). If anything, the crisis has also slowed the development of blended learning in universities, including the use of MOOCs or other forms of online learning, in addition to “old-fashioned” classroom learning.…”
Section: University Outcomes Affected By the Crisismentioning
confidence: 99%